Estimating the Relationship between Particulate Matter and MODIS AOT in the Bangkok Metropolitan Region, Thailand - Boongla, Yaowatat (Science & Technology Asia, 2023)
Bangkok (BKK) and Pathumthani (PT), Thailand, have faced air pollution problems every year. The main factors contributing to air pollution emissions in BKK and PT are vehicles, industries, open burning, and agricultural residual burning. Air quality monitoring stations in BKK and PT are limited, and some regions have no stations, so this research would like to solve that problem. The research effort is to estimate the dispersion of coarse and fine particles (PM10 and PM2.5) in the atmosphere in BKK and PT from January 2018 to May 2020. PM10 and PM2.5 levels were collected from 13 stations that were investigated before the COVID-2019 Lockdown. The results of this study show the average PM10 concentrations in the range 19.36-55.47 μg/m-3, while the average PM2.5 concentrations are found in the range 6.33-22.80 μg/m-3. The correlation of PM10 and PM2.5 at ground-based stations and PM10 and PM2.5 from the aerosol optical thickness (AOT) retrieved by the Moderate Resolution Imaging Spectroradiometer (MODIS). Results reveal positive correlations with correlation coefficients (R2) equal to 0.398 and 0.560 for PM10 and PM2.5, respectively. The Pearson correlation coefficient was used to explore the influence of meteorological factors on PM10 and PM2.5 concentrations. The correlation results presented positive relationship, major factors were pressure, temperature, RH and wind speed. Multiple regression analysis (MRA) stepwise shows that meteorological factors affected PM10 concentrations at 68.10% with high relative values for pressure, RH, visibility, and AOT, and PM2.5 concentrations at 50.20% with high relative values for wind speed and could cover, respectively (p < 0.01).